What is political about jurisprudence? Courts, politics and political science in Europe and the United States - Rheder, Britta (Köln, 2007)
"This paper reflects on the literature on courts and politics in Europe and the United States. US-American Political Science has dealt for over fifty years with the role of courts and judges as political actors, whereas this perspective has only recently emerged in Europe. The debates differ not only with regard to the number of articles written, but also with regard to their content. This paper discusses the different research perspectives that are being pursued on both sides of the Atlantic. While a major part of the US-American literature investigates the politics of judicial action and the politicization of the legal system, research on European courts confines itself to analyzing the effects of judicial action, often describing them in terms of juridification. Based on a review of the existing literature, this paper suggests that European scholars ought to take crucial assumptions of the US-American research tradition more seriously."